Purchase intention and purchase behavior online : a cross-cultural approach (2020)
This article aims to explore the key factors on e-commerce adoption from elements of social psychology, such as attitude, subjective norms, perceived behavioral control, ease of use and perceived usefulness, introducing the study of non-traditional elements like buying impulse, compatibility, and self-efficacy in online stores, contrasting relationships in a cross-cultural environment. The proposed model is tested from quantitative research with a sample of 584 online consumers in Colombia and Spain. The following statistical analyses were conducted: CFA, structural equations, measurement instrument invariance, and multi-group analysis with EQS 6.3 software. The study reveals that self-efficacy in online stores is a key factor in adopting electronic commerce above the cultures studied. Also, there is significant evidence that proves the moderating effect of national culture on several relationships of the model proposed. Results highlight the importance of national culture to understand impulsive buying behavior. The article presents several considerations toward the main elements to generate online purchase intention among consumers in an emerging country and finds substantial differences with consumers in a developed country. Practical implications are made for companies to adopt online channels and expand internationally.